Who I am asking about: What the sentence endings imply about the unexpressed subjects in wh-questions - Izutsu, Katsunobu; Kim, Yong-Taek (Investigationes Linguisticae, 2019)
This study demonstrates that the sentence endings of Korean and Japanese wh-questions can be analyzed as serving to evoke and, in a weaker sense, to mark an unexpressed verb subject. This study further contends that the endings are not complex forms with successive morphemes each contributing to the whole meaning but rather simplex forms each of which has its own meaning and function. This study argues that pragmatic groupings of event participants help the sentence endings to mark subjects in the Korean and Japanese languages as well as other languages of the world.